2002
DOI: 10.1107/s0907444902016566
|View full text |Cite
|
Sign up to set email alerts
|

The structures ofMicrococcus lysodeikticuscatalase, its ferryl intermediate (compound II) and NADPH complex

Abstract: The crystal structure of the bacterial catalase from Micrococcus lysodeikticus has been re®ned using the gene-derived sequence both at 0.88 A Ê resolution using data recorded at 110 K and at 1.5 A Ê resolution with room-temperature data. The atomic resolution structure has been re®ned with individual anisotropic atomic thermal parameters. This has revealed the geometry of the haem and surrounding protein, including many of the H atoms, with unprecedented accuracy and has characterized functionally important hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 44 publications
7
72
0
1
Order By: Relevance
“…EXAFS studies of other compound II analogues indicated short iron-oxygen bonds in a model complex (36), in myoglobin peroxide (40), and in cytochrome c peroxidase ES complex (41), each of which has a ferryl-oxo moiety without a porphyrin radical cation. Long iron-oxygen bonds (1.84-1.92 Å) were reported from x-ray crystal structure studies of the compound II derivatives of HRP (43), myoglobin (44), and catalase (45) and also the compound I derivative of cytochrome c peroxidase (46), but Green (47) noted that the x-ray crystal structure results are in conflict with EXAFS, Raman spectral, and computational results and suggested that the long iron-oxygen bonds might have resulted from reduction of the ferryl species to ferric or ferrous species in the x-ray beam.…”
Section: Resultsmentioning
confidence: 99%
“…EXAFS studies of other compound II analogues indicated short iron-oxygen bonds in a model complex (36), in myoglobin peroxide (40), and in cytochrome c peroxidase ES complex (41), each of which has a ferryl-oxo moiety without a porphyrin radical cation. Long iron-oxygen bonds (1.84-1.92 Å) were reported from x-ray crystal structure studies of the compound II derivatives of HRP (43), myoglobin (44), and catalase (45) and also the compound I derivative of cytochrome c peroxidase (46), but Green (47) noted that the x-ray crystal structure results are in conflict with EXAFS, Raman spectral, and computational results and suggested that the long iron-oxygen bonds might have resulted from reduction of the ferryl species to ferric or ferrous species in the x-ray beam.…”
Section: Resultsmentioning
confidence: 99%
“…Refinements, including rigid body, simulated annealing, and conjugate gradient minimizations with CNS, and model improvements in O (63), were performed initially for some structures. Further steps included multiple cycles of restrained refinement in Refmac (58,64) and model building in Coot (65) and addition of water molecules by ARP/ wARP (66). In the later stages TLS refinement was introduced, and finally restrained anisotropic refinement performed with Refmac (67,68).…”
Section: Methodsmentioning
confidence: 99%
“…[4] As both intermediates feature a Fe IV =O bond, it is expected that they have a similar FeÀO bond length. However, two recent high-resolution crystal structures of Cpds I and II give quite different FeÀO distances, 1.67 and 1.86 , respectively, [4,6,7] with a r.m.s.d. of 0.02 .…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1. Structure around the active site of heme catalases (the residue numbering of MLC is used [6] ). Scheme 1.…”
Section: Introductionmentioning
confidence: 99%